Application of Polymerase Chainreaction (PCR) In Diagnosis of Malignant Catarrhal Fever (MCF) in Indonesia - Saepulloh, Muharam; ., Darminto (Indonesian Bulletin of Animal and Veterinary Sciences, 1999)
Malignant catarrhal fever (MCF) is a fatal viral disease of cattle, buffalo and other ruminants characterized by proliferation and infiltration of lymphocytes and followed by necroses of infected organs . According to the aetiological of the agents, MCFis classified into two types: wildebeest-associatedMCF(WA-MCF) which is caused by Alcelaphinae herpesvirus-1 (AHV-1) and sheep-associated MCF (SA-MCF) which is caused by Ovine herpesvirus-2 (OHV-2). Most MCF cases in Indonesia is SA-MCF. Due to the intact virus of SA-MCF has not been able isolated, the diagnosis of this disease is based on the clinical signs and pathological changes. However, a segment of DNA virus of SA-MCF has been isolated from MCF cases in rabbit, deer, and cattle which provided an opportunity to study a DNA sequencing and led to the development of diagnostic technique based on the molecular biology, Polymerase Chain Reaction (PCR). The PCR technique was able to detect segments of DNA of SA-MCF virus in infected organs . This publication describes the application of PCR for diagnosis of SA-MCF inÂ  Indonesia. Key words : MCF, PCR, diagnosis, cattle, buffalo